Critical moment manifestations In perpendicular lines (Journal of the College of Basic Education, 2022)
Manifestations of the critical moment in orthogonal lines The critical moment is one of themost difficult moments that pass on the human being determines his fate in existence Vbostaatha the options in front of him there is no way but death as the storyteller Hassan Karim Ati in the entrance, which is a wide entrance and then stands in front of three degrees and the other most important hostile And the hostile. environment and the critical moment we can through what is the critical moment that we reach the conclusion and highlighting the most important key points in the lines clearly orthogonal was a successful group compared to criticism.Key words: manifestations, roommate moment, perpendicular lines.1 - manifestations: clarity in the vision, the emergence of what was submerged deep into existence.2 - The critical moment: we mean the death to which the human resort to forced and not voluntary.3 - orthogonal lines: It is the first story collection of the storyteller Hassan Karim Aati.